EFFECT OF SUGAR CANE MORDANT ON THE DYEING OF TEXTILE COLORS USING EXTRACT OF THE SHY PRINCESS PLANT (Mimosa Pudica) - Rosyadi, Farhana Lafaticha; Adriani, Adriani (Universitas Negeri Yogyakarta, 2024)
This study explores the use of natural color sources from the sensitive plant (Mimosa Pudica) with different sugar cane mordants to reduce pollution caused by synthetic dyes. The research aims to examine the color evenness and the impact of different mordants on cotton material dyeing using sensitive plant extracts and black, red, and yellow sugar cane mordants. The study adopts an experimental approach and collects primary data from 15 panelists. The results show that the use of black, red, and yellow sugar cane mordants leads to very flat color flatness. The evenness of color is also significant, with a data value of 0.011 <0.05, suggesting a significant effect on the dyeing process of sensitive plant (Mimosa Pudica) extract using black, red, and yellow sugar cane mordants on cotton material.